Hormonal vs. Non-Hormonal Contraceptives for Women in Relation to Cervical Cancer: A Systematic Review - Rusfandi, Annisa Adhania; Agung Indrawan, I Wayan (Fakultas Kedokteran Universitas Brawijaya, 2025)
Recent global statistics indicate approximately 527,624 new cases of cervical cancer and 265,672 deaths annually. Additionally, recent research has identified a correlation between cervical cancer incidence and the use of hormonal or non-hormonal contraceptives. This systematic review aims to investigate this correlation. Articles meeting inclusion criteria from Google Scholar and PubMed within the last five years were searched. Eight eligible studies were included: six on hormonal contraceptives and two on non-hormonal contraceptives. The review findings suggest that the use of both non-hormonal and hormonal contraceptives increases the risk of cervical cancer. Non-hormonal contraception was associated with a slightly elevated risk, while hormonal contraceptives, especially oral contraceptive tablets used over an extended period, showed a clear link to increased cervical cancer risk.